Could an increase in education raise income inequality? : evidence for Latin America - Battistón, Diego Ezequiel (2014)
This paper explores the direct effect of an education expansion on the level of earnings inequality by carrying out microsimulations for most Latin American countries. We find that the direct effect of the increase in years of education in the region in the 1990s and 2000s was unequalizing; this result is expected to hold for future expansions if increases in education are not highly progressive. Both facts are closely linked to the convexity of returns to education in the labor market. On average, the estimated impact of the education expansion remains unequalizing when allowing for changes in returns to schooling, although the effect becomes smaller.